Exclusive breastfeeding and its association with pre- and postnatal factors: a cohort prospective study - de Melo, Letícia Santos Alves [UNESP]; Silva, Lorena Fonseca [UNESP]; da Silva, Silvio Rocha Corrêa [UNESP]; Rosell, Fernanda Lopez [UNESP]; Júnior, Aylton Valsecki [UNESP]; Zuanon, Angela Cristina Cilense [UNESP]; da Silva Tagliaferro, Elaine Pereira [UNESP] (Universidade Estadual de Campinas, 2024)
Aim: This cohort study aimed to investigate the exclusive breastfeeding (EBF) prevalence and its association with maternal EBF intention and other variables. Method: Pregnant women (n=653) in the third trimester of pregnancy filled out a questionnaire on EBF intention using the Infant Feeding Intentions scale and other variables. After delivery, mothers were contacted by phone at the first (T1; n=467), third (T3; n=333), and sixth (T6; n=217) month of the baby’s life or until breastfeeding was terminated, to collect data on breastfeeding, delivery, the newborn, oral habits, and family variables. The associations between independent variables and the outcomes (EBF prevalence at T1, T3, and T6) were analyzed by simple and multiple logistic regression models (α =0.05). Results: EBF prevalence was 81.2% at T1, 64.0% at T3, and 35.9% at T6. Nott use baby bottle (OR=612.59; OR=139.08; OR=15.05) and no pacifier use (OR=2.94; OR=2.78; OR=2.93) were associated with the outcome at T1, T3, and T6, respectively. Other associated variables were strong EBF intention (OR=1.71) at T1; higher birth weight (OR=1.62), childcare support (OR=2.59), maternal age (OR=0.54), being married or having a partner (OR=1.82) at T3; and not returning to work (OR=2.39) at T6. Conclusion: The EBF prevalence was high at the first month of the baby’s life and decreased over six months. The EBF intention affected EBF initiation. Variables related to the mother’s demographic characteristics, the baby’s birth weight, the childcare support or the baby bottle/pacifier use were associated with EBF.
Keywords: Behavior; Breast feeding; human; Infant food; Intention; Milk